(7x-2)-x=68

Simple and best practice solution for (7x-2)-x=68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-2)-x=68 equation:


Simplifying
(7x + -2) + -1x = 68

Reorder the terms:
(-2 + 7x) + -1x = 68

Remove parenthesis around (-2 + 7x)
-2 + 7x + -1x = 68

Combine like terms: 7x + -1x = 6x
-2 + 6x = 68

Solving
-2 + 6x = 68

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 6x = 68 + 2

Combine like terms: -2 + 2 = 0
0 + 6x = 68 + 2
6x = 68 + 2

Combine like terms: 68 + 2 = 70
6x = 70

Divide each side by '6'.
x = 11.66666667

Simplifying
x = 11.66666667

See similar equations:

| 2-7m-6m= | | -(7-x)-(7-x)=2x+14 | | .33*x=6700 | | -1=s/3-5 | | h(t)=-16t^2+112t+10 | | ​2/1a=11 | | 8x-18=14x+24 | | 21-6(7y-4)=-40x+45 | | 3/4x-1/2=x-7/4 | | (2t)(81t^1/2) | | 9+7d-5-8d= | | 20-26x=6x^2 | | f(5)=-4x+12 | | 3/4x-1/2=x-7/7 | | 4x=380 | | 1/3×x=6700 | | 2+6f=8 | | 89-2x=67 | | 7x-2x+10x+45=75 | | x-(8)=3x | | 3(b+2)+9=3b+15 | | (3x+8)+(4x+2)= | | 53x=795 | | 1/bxb | | 3(m-5)+5= | | (3b+5)+2b= | | 3x+2y+2z=360 | | 5x+7(8-x)=50 | | -(3-y)-(3+y)=2y-6 | | 2+5x=2y+10 | | n^2-3=14n | | 52-2x=8 |

Equations solver categories